Market imperfections and land productivity in the Ethiopian Highlands - Holden, Stein; Shiferaw, Bekele; Pender, John L. (2001)
This study analyzes how market imperfections affect land productivity in a degraded low-potential cereal- livestock economy in the Ethiopian highlands. A wide array of variables is used to control for land quality in the analysis. Results of three different selection models were compared with least squares models using the HC3 heteroskedasticity-consistent covariance matrix estimator. Market imperfections in labor and land markets were found to affect land productivity. Land productivity was positively correlated with household male and female labor force per unit of land. Female-headed households achieved much lower land productivity than male- headed households. Old age of household heads was also correlated with lower land productivity. Imperfections in the rental market for oxen appeared to cause overstocking of oxen by some households. Conservation technologies had no significant positive short-run effect on land productivity. The main results were consistent across the different econometric models.